2009
DOI: 10.1093/jxb/erp003
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the selenium and arsenic metabolic pathways following exposure to the non-hyperaccumulating Chlorophytum comosum, spider plant

Abstract: Although many studies have investigated the metabolism of selenium and arsenic in hyperaccumulating plants for phytoremediation purposes, few have explored non-hyperaccumulating plants as a model for general contaminant exposure to plants. In addition, the result of simultaneous supplementation with selenium and arsenic has not been investigated in plants. In this study, Chlorophytum comosum, commonly known as the spider plant, was used to investigate the metabolism of selenium and arsenic after single and sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Take for example the process of grain filling, over 269 genes may play a functional role, but how and at what concentration As induces phenotypic changes is not well-defined (48). The situation is further complicated by the interconversion of metal(loid) species and their species specific uptake, translocation and interaction characteristics (49). What is apparent, however, is that As has a negative influence on plant metabolism at much lower concentrations than can be detected by comparing general growth features alone (50).…”
Section: Discussionmentioning
confidence: 99%
“…Take for example the process of grain filling, over 269 genes may play a functional role, but how and at what concentration As induces phenotypic changes is not well-defined (48). The situation is further complicated by the interconversion of metal(loid) species and their species specific uptake, translocation and interaction characteristics (49). What is apparent, however, is that As has a negative influence on plant metabolism at much lower concentrations than can be detected by comparing general growth features alone (50).…”
Section: Discussionmentioning
confidence: 99%
“…Selenate is actively taken up and transported easily to the shoot, where some of it is reduced and assimilated into selenoamino acids in chloroplasts. Selenite enters plant cells passively and the bulk of it is nonenzymatically reduced and metabolized primarily in roots (Zayed et al, 1998;Afton et al, 2009). Notably, when the transgenic plants were treated with selenate, the BoCOQ5-2 transformants accumulated significantly less total Se despite the observation of no increased rate of Se volatilization in comparison with the vectoronly control.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the leaves of this plant have a high sorption characteristics with respect to formaldehyde, carbon monoxide, benzene, trichlorethylene, phenols and other compounds [4,3]. By chemical analysis of the enzymatic hydrolyzate of Chlorophytum comosum in its composition was found DL -ornithine monohydrochloride having desintoxication and hepatoprotective action [7,8,11,15,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…To test the hypothesis about the effectiveness of bio-stimulation, we carried out a study which purpose was to examine the severity of liver damage while taking CCl 4 and enzymatic hydrolyzate of Chlorophytum comosum (L.).…”
Section: Introductionmentioning
confidence: 99%